PENGARUH BEBERAPA JENIS MULSA ORGANIK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) VARIETAS TRINITARIO - Fajri, Arnil; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research to deternine the effect of the use of some types organic mulch on the growth seedings of cacao (Theobroma cacao L.) varieties of Trinitario and know the best mulching. This study was conducted in Experimental Field of Faculty of Agriculture, University ofÂ  Riau which lasts from march to June 2016. The study was conducted in a completely randomized design (CRD) consisting of 4 treatments, each treatment was repeated 5 times to 20 experimental units per finding unit compristing three plants so grand total of 60 plants cocoa. The treatments were without organic mulch (M0), organic mulch paddy straw 150 g/ plant (M1),organic mulch sawdust 150 g/ plant (M2) and organic mulch paddy straw 75 g/ plant+ sawdust 75 g/ plant parameters measured were plant height, number of leaves, leaf area, stem diameter. The data were statistically analyzed using of variance (ANOVA). Effect of organic mulch of paddy straw with a dose of 150 g/ plant significantly different from provision of organic mulch of saw dust at a dose of 150 g/ plant organic paddy straw mulching 75 g/ plant sawdust 75 g/ plant and without offering of organic mulch. Biological mulching paddy straw with a dose of 150 g/ plant will give the best effect on plant height, number of leaves, leaf area and stem diameter.Key words: cocoa, organic mulch, Trinitario varietiesÂ